Rural Health Response and Community Preparedness for the Covid-19 Pandemic - Nita Arisanti; Trevino A Pakasi; Syarhan Syarhan (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Covid-19  is  a  highly  contagious  disease  and  has  infected more than seven million people worldwide. Deaths due to this  disease  have  reached  418,000  deaths  in  June  2020.1 Based on data from the Indonesian Covid-19 Task Force, there were 172,053 cumulative cases with a death rate of 4.3% in Indonesia up to August 30, 2020.Indonesia  is  an  archipelago  country  which  has  different geographical  characteristics. Currently,  access  to  basic healthcare  and  quality  of  basic  health  services  has  not reached  all  regions,  especially  those  in  underdeveloped, remote  and  archipelago  areas. Health  problems  in  rural areas become a concern for Indonesian government. This is because around 43% of people live in rural areas or around 116  million  people.  Government  should pay  attention  to rural  health  problems  as  well  as  urban  health.  Likewise, during  the Covid-19  pandemic  rural  area  will  face  same problems to Covid-19.